On the disappearance of the singularities of analytic functions - Chawinson, S.; Kochetkow, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. Я. Хавинсон, А. Н. Кочетков. О стирании особенностей аналитических функций некоторых классов S. Chavinsonas, A. Kočetkovas. Analizinių funkcijų pavienumų išnykimo klausimu